Besonderes Verwaltungsrecht und ökonomische Theorie - Christoph Engel (Max Planck Institute for Research on Collective Goods, 2011)
– The novel part of this paper is a model of the principle of proportionality, as the cornerstone of the doctrine of fundamental rights. German law, and with some modifications also the law of the European Community and the European Convention on Human Rights, do not categorically outlaw interventions into fundamental freedoms and human rights (as, in principle, the US doctrine). Rather a state measure that is classified as an intervention comes under the scrutiny of the Constitutional Court, the European Court of Justice or the European Court of Human Rights. All courts clear interventions only if government can show that they serve a legitimate aim, and that the concrete measure is conducive to this aim, is least intrusive, and appropriately balances the importance of the legitimate aim with the severity of the intervention. While the doctrine on all these elements is rich, many questions are unsettled. This paper uses simple concepts from microeconomic theory to formalize the steps, and thereby to clarify the doctrine.
Keywords: H41; D01; D02; A12; K10; D61; 330; principle of proportionality; human right; fundamental freedom; law and economics of constitutional law; Verwaltungsrecht; Staatsrecht; Rechtsprechung; Rechtsökonomik; Positive Ökonomik; Normative Ökonomik